Enhancing Purchasing Decisions Through Reliability and Responsiveness: Exploring Customer Satisfaction as A Mediating Factor for Indonesian Expedition - Edhie Budi Setiawan; Siti Nurhayat; Zihan Intan Maghfira; Mayla Faiza Ningtyas (Green Publisher, 2025)
The expedition sector plays a crucial role in the global economy by enabling the movement of goods. JNE, a leading expedition company in Indonesia, faces consumer complaints about service quality, such as delivery delays (reliability) and poor handling of goods (responsiveness). The purpose of this study examines the impact of reliability and responsiveness on purchasing decisions, with customer satisfaction as a mediating factor. Using a quantitative approach, data were collected via online questionnaires from 204 respondents through purposive sampling and analyzed using Partial Least Squares-Structural Equation Modeling (PLS-SEM). The findings reveal that both reliability and responsiveness significantly influence purchasing decisions, with customer satisfaction strengthening this relationship. To improve customer purchasing decisions, JNE should prioritize responsiveness, as it is the most influential variable, along with maintaining reliability and customer satisfaction. This research contributes that responsiveness and reliability are crucial for the delivery service industry as they can influence satisfaction and purchase decisions in the service.